Regulating net zero: from groundswell to ground rules - Hale, T; Wetzer, T; Abebe, SK; Allen, M; Amel-Zadeh, A; Armour, J; Axelsson, K; Caldecott, B; Dias, L; Fankhauser, S; Franta, B; Hepburn, C; et al. (Springer Nature, 2024)
Following a groundswell of voluntary net-zero targets by companies, regulators are increasingly introducing mandatory rules. If governments can overcome the barriers to rigour, coherence and fairness, such mandatory ‘ground rules’ have the potential to overcome the obstructionism that holds back a just climate transition.